Fabrication and Characterization Glass/AZO/Ag Ultraviolet Photodetector - Upadhyay, Rishibrind Kumar; Sharma, Shivani (International Conference on Signal Processing and Communication (Online), 2025)
In this article, we demonstrate the succinct report on Al-doped Zinc Oxide (AZO) and pristine Zinc Oxide (ZnO) based ultraviolet photodetector device fabrication on the glass substrate. Pristine Zinc oxide (ZnO) and Al-doped ZnO (AZO) nanoparticles were prepared using a simple chemical sol-gel route. The prepared ZnO and Al-doped ZnO (AZO) nanoparticles have been characterized using XRD, and high-resolution SEM for phase formation, and surface morphology respectively. XRD graph confirmed the formation of the wurtzite hexagonal structure of ZnO. The device performance was measured using a semiconductor parametric analyzer with a UV light source for -2V to 2V.